Adoption of Green Industrial Internet of Things to Improve Organizational Performance: The Role of Institutional Isomorphism and Green Innovation Practices - Xu, Nan; Fan, Xingyu; Hu, Rui (Frontiers in Psychology, 2022)
Emerging technology developments and functions of the internet of things (IoT) in industrial systems are leading the development of the Industrial IoT (IIoT). Greener – cleaner environmental goals can be achieved by putting green IIoT (GIIoT) into practice. This research aims to explore the reasons for the adoption of GIIoT in organizational decision-making and to explore its impact on organizational performance. The proposed research model was tested by collecting data through a structured questionnaire. The findings suggest that institutional isomorphism has a positive impact on the adoption of GIIoT. Moreover, GIIoT is positively associated with green innovation practices (product, process, and management) that lead to organizational performance. The potential impact of various types of institutional isomorphism described in this study can help organizations better comprehend the institutional pressures they enforce and/or appease their stakeholders — especially as they adopt GIIoT — to manage production issues and potential compliance pressures in the process.